Teacher’s perceptions for pedagogical mediation in videoconferences at Universidad Estatal a Distancia (UNED) - Salas-González, Silvia (Innovaciones Educativas, 2020)
The article analyzes the importance that those who give videoconferences at the State Distance University (UNED) should be aware of the need to rethink the methodological strategies proposed by them in the development of each of the scheduled sessions. Therefore, the research aims to design a videoconference proposal as a resource for pedagogical mediation, which teachers can consult and implement in their respective planning. For this purpose, the theoretical framework was based on cooperative and collaborative action research, in which joint work is carried out between researchers and teachers. The main finding demonstrates the need expressed by teachers about receiving induction processes and training to plan and adequately mediate videoconferences. Likewise, it is necessary to have wide guidelines of technical elements and useful pedagogical strategies to present the topics under study in an attractive way.